Author Correction: Deep Learning for Fully-Automated Localization and Segmentation of Rectal Cancer on Multiparametric MR - Stefano Trebeschi; Joost J. M. van Griethuysen; Doenja M. J. Lambregts; Max J. Lahaye; Chintan Parmar; Frans C. H. Bakers; Nicky H. G. M. Peters; Regina G. H. Beets-Tan; Hugo J. W. L. Aerts (Scientific Reports, 2018)
A correction to this article has been published and is linked from the HTML version of this paper. The error has been fixed in the paper.